Voltage Quality in Electrical Power Systems - Schlabbach, J.; Blume, D.; Stephanblome, T. (Power and Energy series v.36, 2001)
Problems of voltage quality and their solutions are becoming increasingly important with the growth in power electronics and the high sensitivity of electronic equipment. Translated and updated from the German original published by VDE-Verlag, this book successfully details the theoretical and practical background to low voltage conducted disturbances including harmonics, voltage fluctuation/flicker and asymmetrical voltages. Each chapter is illustrated with practical examples and exercises based on the authors' experience of application problems, including measurement, assessment and remedial measures. The book is set in the context of European standards. This book will be of interest to electrical engineers in industry, utilities and universities, as well as companies interested in planning, operating and designing power system equipment.